WHO laboratory validation of Xpert® CT/NG and Xpert® TV on the GeneXpert system verifies high performances. Issue 12 (19th November 2018) - Jacobsson, Susanne; Boiko, Iryna; Golparian, Daniel; Blondeel, Karel; Kiarie, James; Toskin, Igor; Peeling, Rosanna W.; Unemo, Magnus
Abstract : Effective tests for diagnosis of sexually transmitted infections (STIs), used point of care to inform treatment and management decisions, are urgently needed. We evaluated the analytical sensitivity and specificity of the Xpert ® CT/NG and Xpert ® TV tests, examining 339 samples spiked with phenotypically and/or genetically diverse strains of Neisseria gonorrhoeae, Chlamydia trachomatis, and Trichomonas vaginalis, and other related species that may cross‐react. The APTIMA Combo 2 test and APTIMA TV test were used as reference tests. The analytical sensitivity for all three agents in the Xpert ® CT/NG and Xpert ® TV tests was ≤10 2 genome equivalents/reaction. The analytical specificity of both tests was high. False‐positive results were identified in the Xpert ® TV test when challenging with high concentrations of Trichomonas tenax, Trichomonas gallinae, Trichomonas stableri, and Trichomonas aotus . However, the clinical relevance of these cross‐reactions can likely be neglected, because these species have not been identified in urogenital samples from humans. In conclusion, the analytical sensitivity and specificity of the user‐friendly Xpert ® CT/NG and Xpert ® TV tests on the GeneXpert system were high. The results support the use of specimens from also extra‐genital sites, for example, pharynx and rectum. However, appropriate clinical validations are additionally required.